A new series of mononuclear lanthanide single molecule magnets based on sandwich-type germanomolybdates [Ln(GeMo11O39)2]13− (Ln = ErIII, GdIII, DyIII or TbIII). (18th October 2017) - Jin, Zhanbin; Bai, Jie; Wei, Tingting; Li, Fengyan; Song, Chunli; Luo, Xinze; Xu, Lin
Abstract : New series of mononuclear lanthanide single molecule magnets based on sandwich-type germanomolybdates have been synthesized and their magnetic properties were investigated. Abstract : A new series of mononuclear lanthanide single molecule magnets based on sandwich-type germanomolybdates, (C4 H10 ON)8 H5 [Er(GeMo11 O39 )2 ]·14H2 O (1 ), (C4 H10 ON)8 H5 [Gd(GeMo11 O39 )2 ]·13H2 O (2 ), (C4 H10 ON)8 H5 [Dy(GeMo11 O39 )2 ]·15H2 O (3 ), (C4 H10 ON)8 H5 [Tb(GeMo11 O39 )2 ]·14H2 O (4 ), have been successfully synthesized. Compounds1–4 are the first examples of the coordination assembly of monolacunary germanomolybdates and heavy rare earth elements, and were structurally characterized by single-crystal X-ray diffraction analyses. The magnetic investigation shows that1 and3 exhibit magnetic relaxation behavior in a zero applied dc field, indicative of SMM behavior. Slow magnetic relaxation behavior of1–4 could be observed in a static magnetic field of 5000 Oe.